Waterproof and breathable non-asphalt-based composition, non-asphalt-based sizing and method for preparing same, waterproof roll goods and applications thereof
Patent Information
- Application Number
- CN202610937949.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-20
AI Technical Summary
第一,传统防水材料形成连续密闭的防水屏障,卷材结构内部及基层中产生的水汽无法排出,易在防水层与基层之间积聚,形成水汽滞留
(1)本发明提供的非沥青基胶料,通过采用由改性纳米碳酸钙和改性空心微珠组合形成的功能填料,使制备得到的防水卷材的微孔孔径远小于液态水滴,静水压≥1500mmH2O,防水密封性能优异,同时具有优异的透气性,解决了现有卷材“防水不透气”的技术难题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer waterproof materials technology, specifically to a waterproof and breathable non-asphalt-based adhesive composition, a non-asphalt-based adhesive and its preparation method, and waterproof membranes and their applications. Background Technology
[0002] Traditional waterproofing materials mostly adopt a dense film-forming or solid structure, which usually only has a waterproof effect and generally does not have a breathable function. The following technical defects may exist in the use of these materials: First, traditional waterproofing materials form a continuous and sealed waterproof barrier, which prevents moisture generated inside the roll structure and the base layer from escaping. This moisture tends to accumulate between the waterproofing layer and the base layer, resulting in moisture retention.
[0003] Secondly, as the ambient temperature changes, the trapped moisture generates pressure, which can easily cause the waterproof layer to bulge or become hollow, leading to a failure in adhesion to the substrate. Long-term use can easily cause the waterproof layer to crack, peel, and break, reducing the overall stability and service life of the waterproof system.
[0004] Third, if moisture is trapped inside the structure for a long time, it will cause the base layer to become damp, moldy, and damp, affecting the durability of the building structure and the comfort of the user environment.
[0005] CN114907783A discloses a PE / POE composite self-adhesive waterproof membrane, its preparation method, and its application. The waterproof membrane includes a PE / POE composite membrane, self-adhesive, and a protective liner. The self-adhesive is uniformly coated on the lower surface of the PE / POE composite membrane, and the coating thickness of the self-adhesive is 0.1-0.5 mm. The total thickness of the PE / POE composite membrane, self-adhesive, and protective liner is 0.4-2.0 mm. The self-adhesive comprises the following raw materials in parts by weight: 35-45 parts epoxy acrylate resin, 15-20 parts polyurethane prepolymer, 0.1-0.5 parts dibutyltin dilaurate, 10-15 parts EVA resin, and 8-10 parts thermoplastic elastomer SBS. In this method, polyurethane prepolymer and epoxy acrylic resin cross-link and cure to form a dense material system, giving the material high strength and high tensile strength. However, the air permeability of the roll is obviously insufficient, and the curing conditions of the flexible component and the rigid component are different, resulting in compatibility defects and affecting the service life of the roll.
[0006] In summary, developing a new type of waterproof membrane with excellent waterproof and breathable properties as well as high adhesion is of great significance. Summary of the Invention
[0007] The purpose of this invention is to provide a waterproof membrane with excellent waterproof and breathable properties as well as high adhesion.
[0008] To achieve the above objectives, a first aspect of the present invention provides a waterproof and breathable non-asphalt-based adhesive composition, the composition comprising a main agent and an auxiliary agent, wherein the main agent includes an elastomer base material, a tackifying resin, a plasticizer, and a functional filler. Based on the total mass of the composition, the content of the elastomer base material is 10-20 wt%, the content of the tackifying resin is 15-25 wt%, the content of the plasticizer is 15-20 wt%, and the content of the functional filler is 30-50 wt%. The elastomer base material includes a first component and a second component in a mass ratio of 1:0.3-1, wherein the first component is a hydrogenated styrene-isoprene copolymer and the second component is an ethylene-octene copolymer and / or an ethylene-vinyl acetate copolymer. The functional filler is formed by combining modified nano-calcium carbonate and modified hollow microspheres in a mass ratio of 2-6:1, wherein the modified hollow microspheres are modified hollow glass microspheres and / or modified hollow ceramic microspheres.
[0009] A second aspect of the present invention provides a method for preparing a waterproof and breathable non-asphalt-based adhesive compound, the method comprising using the components of the composition described in the first aspect above, the method comprising: stirring and mixing the components of the composition to obtain the waterproof and breathable non-asphalt-based adhesive compound.
[0010] A third aspect of the present invention provides a waterproof and breathable non-asphalt-based adhesive prepared by the method described in the second aspect above.
[0011] A fourth aspect of the present invention provides a waterproof and breathable non-bitumen-based waterproof membrane, the waterproof membrane comprising a substrate, a waterproof adhesive layer, and a protective membrane; the waterproof adhesive layer is formed from the waterproof and breathable non-bitumen-based adhesive described in the third aspect above.
[0012] The fifth aspect of the present invention provides the application of the waterproof and breathable non-bitumen-based waterproof membrane described in the fourth aspect above in the field of building waterproofing.
[0013] Through the above technical solution, the present invention has at least the following beneficial technical effects: (1) The non-asphalt-based adhesive provided by the present invention uses a functional filler composed of modified nano-calcium carbonate and modified hollow microspheres to make the micropore size of the prepared waterproof membrane much smaller than that of liquid water droplets, with a hydrostatic pressure ≥1500mmH2O, excellent waterproof sealing performance, and excellent air permeability, thus solving the technical problem of existing membranes being "waterproof but not breathable".
[0014] (2) The non-asphalt-based adhesive provided by the present invention, through the synergistic effect between the components, enables the prepared waterproof membrane to have excellent aging resistance and bonding performance, and significantly extends its service life. Detailed Implementation
[0015] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0016] As mentioned above, a first aspect of the present invention provides a waterproof and breathable non-asphalt-based adhesive composition, which comprises a main agent and an auxiliary agent, wherein the main agent includes an elastomer base material, a tackifying resin, a plasticizer, and a functional filler. Based on the total mass of the composition, the content of the elastomer base material is 10-20 wt%, the content of the tackifying resin is 15-25 wt%, the content of the plasticizer is 15-20 wt%, and the content of the functional filler is 30-50 wt%. The elastomer base material includes a first component and a second component in a mass ratio of 1:0.3-1, wherein the first component is a hydrogenated styrene-isoprene copolymer and the second component is an ethylene-octene copolymer and / or an ethylene-vinyl acetate copolymer. The functional filler is formed by combining modified nano-calcium carbonate and modified hollow microspheres in a mass ratio of 2-6:1, wherein the modified hollow microspheres are modified hollow glass microspheres and / or modified hollow ceramic microspheres.
[0017] According to a preferred embodiment, the elastomeric base material is a combination of hydrogenated styrene-isoprene copolymer, ethylene-octene copolymer, and ethylene-vinyl acetate copolymer in a mass ratio of 1:0.2-0.5:0.2-0.5. The inventors of this invention have discovered that, under this preferred embodiment, the waterproof membrane prepared by this invention exhibits superior adhesion properties and high and low temperature stability.
[0018] In some embodiments, the styrene structural units in the hydrogenated styrene-isoprene copolymer are 36-40 wt%.
[0019] In some embodiments, the ethylene-octene copolymer has a melt flow rate of 2-6 g / 10 min at 190°C and 2.16 kg.
[0020] In some embodiments, the ethylene-vinyl acetate copolymer has a melt flow rate of 350-400 g / 10 min at 190°C and 2.16 kg, and the content of vinyl acetate structural units in the ethylene-vinyl acetate copolymer is 20-40 wt%.
[0021] According to a preferred embodiment, in the functional filler, the modified nano-calcium carbonate is obtained by surface modification of raw nano-calcium carbonate with stearic acid, and the average particle diameter of the raw nano-calcium carbonate is 50-70 nm.
[0022] According to a preferred embodiment, in the functional filler, the modified hollow microspheres are a combination of modified hollow glass microspheres and modified hollow ceramic microspheres in a mass ratio of 1:0.8-1.2.
[0023] According to a preferred embodiment, in the functional filler, the modified hollow microspheres are obtained by hydrophobically modifying raw hollow microspheres with a silane coupling agent, and the average particle diameter of the raw hollow microspheres is 10-20 μm.
[0024] The inventors of this invention have discovered that, under the above-mentioned preferred conditions, modified hollow microspheres can construct more uniform micron-sized microporous breathable channels, and modified nano-calcium carbonate can effectively improve bonding strength and skeleton support. With the synergistic effect of the two, the waterproof membrane provided by this invention has superior waterproof and breathable performance.
[0025] In some embodiments, the modified nano-calcium carbonate is prepared by a method comprising the following steps: A1. Add the raw material nano-calcium carbonate with a water content of less than 1wt% into a high-speed mixer, adjust the temperature to 100-110℃, and add stearic acid; wherein, the mass ratio of raw material nano-calcium carbonate to stearic acid is 50-65:1. A2. At the above temperature, stir and mix at 1000-1500 rpm for 40-60 min to obtain the modified nano-calcium carbonate.
[0026] In some embodiments, the silane coupling agent is selected from at least one of KH-570, KH-560, and KH-550.
[0027] In some embodiments, the modified hollow microspheres are prepared by a method comprising the following steps: B1. Soak the raw material hollow microspheres in a 5-7 wt% NaOH aqueous solution and stir for 3-4 hours to obtain material I; B2. Material I is washed sequentially with an aqueous solution of acetic acid with a concentration of 0.5-2wt% and water, and then dried to obtain material II; B3. Mix the silane coupling agent with an ethanol aqueous solution at a volume ratio of 1:0.8-1.2 for 10-30 min to obtain a hydrolyzed solution; wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:100-200. B4. At 60-70℃, the material II is stirred and reacted with the hydrolysis solution for 1-2 hours. After centrifugation, washing, and drying, the modified hollow microspheres are obtained. The mass ratio of the raw material hollow microspheres to the silane coupling agent is controlled to be 1:0.03-0.05.
[0028] Preferably, the tackifying resin is a combination of terpene phenolic resin and hydrogenated C5 petroleum resin in a mass ratio of 1.5-3:1. The inventors of this invention have discovered that, in this preferred embodiment, the waterproof membrane provided by this invention can achieve a synergistic improvement in initial tack, holding power, and bonding strength.
[0029] Preferably, the plasticizer is formed by compounding polybutadiene and naphthenic oil, wherein the molecular weight of the polybutadiene is 3000-3500.
[0030] More preferably, the plasticizer is a mixture of polybutadiene and naphthenic oil in a mass ratio of 1:0.4-0.6.
[0031] More preferably, the content of polycyclic aromatic hydrocarbons in the naphthenic oil is <1 wt%.
[0032] In some embodiments, the adjuvants include antioxidants and light stabilizers; the antioxidant content is 1-2 wt% and the light stabilizer content is 1-2 wt% based on the total mass of the composition.
[0033] Preferably, the antioxidant is a combination of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.8-1.2.
[0034] Preferably, the light stabilizer is UV-327 and / or UV-531, which are ultraviolet absorbers.
[0035] As previously stated, a second aspect of the present invention provides a method for preparing a waterproof and breathable non-asphalt-based adhesive compound, the method comprising using the components of the composition described in the first aspect above, the method comprising: stirring and mixing the components of the composition to obtain the waterproof and breathable non-asphalt-based adhesive compound.
[0036] According to one specific embodiment, a method for preparing a waterproof and breathable non-asphalt-based adhesive includes the following steps: (1) Place the elastomer base material in a high-speed kneader and melt-mix it for 10-15 minutes at a speed of 300-400 rpm and a temperature of 120-130℃ to obtain the elastomer melt; (2) Keeping the temperature and rotation speed constant, add the tackifying resin and plasticizer to the elastomer melt in sequence, stir and mix for 10-40 minutes to obtain material I; (3) Under the conditions of 500-600 rpm and 120-130℃, the functional filler is mixed with the material I and sheared and stirred for 10-40 min to obtain material II; (4) Under the conditions of 300-400 rpm and 140-150℃, the additives are mixed with the material II and stirred for 5-10 min to obtain the waterproof and breathable non-asphalt-based adhesive.
[0037] In some embodiments, step (1) further includes drying the elastomeric base material to which the melt mixing is performed, wherein the drying conditions include a temperature of 60-70°C and a time of 2-3 hours.
[0038] In some embodiments, in step (3), the functional filler is added in steps: first, the modified nano-calcium carbonate is mixed with the material I, and sheared and stirred for 20-25 minutes, then the modified hollow microspheres are added, and shearing and stirring is continued for 10-15 minutes to obtain the material II.
[0039] As previously stated, a third aspect of the present invention provides a waterproof and breathable non-asphalt-based adhesive prepared by the method described in the second aspect above.
[0040] As previously described, a fourth aspect of the present invention provides a waterproof and breathable non-bitumen-based waterproof membrane, the waterproof membrane comprising a substrate, a waterproof adhesive layer, and a protective membrane; the waterproof adhesive layer is formed from the waterproof and breathable non-bitumen-based adhesive described in the third aspect above.
[0041] Preferably, the substrate is a PP-EPE-PP three-layer composite waterproof and breathable base film.
[0042] Preferably, the protective layer is a PE isolation film and / or a PA film.
[0043] In some embodiments, the steps for preparing the waterproof and breathable non-bitumen-based waterproof membrane include: heating the waterproof and breathable non-bitumen-based adhesive to 140-160°C using a hot melt adhesive coating machine, and coating the molten adhesive onto both the upper and lower surfaces of the substrate, controlling the coating amount to be 180-250 g / m². 2 Then, an isolation protective film is applied to the upper and lower surfaces after coating, and the thickness of the roll is controlled to be 1.2mm to obtain the waterproof and breathable non-asphalt-based waterproof roll.
[0044] As previously stated, the fifth aspect of the present invention provides the application of the waterproof and breathable non-bitumen-based waterproof membrane described in the fourth aspect above in the field of building waterproofing.
[0045] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the invention is now described in detail through embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention, and the scope of protection of this invention is not limited to the following description. In the following examples, unless otherwise specified, all raw materials and reagents used are common commercially available products.
[0046] The following examples include some of the raw materials used and their sources: Hydrogenated styrene-isoprene copolymer (SEPS): molecular weight 165,000, styrene structural unit content 37 wt%, grade or product number YH-4010, purchased from Baling Petrochemical Company. Ethylene-octene copolymer (POE): melt flow rate (190°C, 2.16 kg) is 3.6 g / 10 min, product number DF740, purchased from Mitsui Chemicals, Japan; Ethylene-vinyl acetate copolymer (EVA): molecular weight 10000, melt flow rate (190℃, 2.16kg) 400 g / 10min, vinyl acetate structural unit content 28wt%, grade or product number EV 210, purchased from Mitsui Chemicals, Japan. Terpene phenolic resin: Product number BX-920, purchased from Foshan Baolin Chemical Co., Ltd.; Hydrogenated C5 petroleum resin: Product number H5-1000, purchased from Henghe Materials Technology Co., Ltd. Polybutadiene: molecular weight 3200, catalog number NISSO-PB B-3000, purchased from Japan Soda Corporation; Naphthenic oil: 0.8 wt% polycyclic aromatic hydrocarbon content, product number 4010, purchased from Wuxi Fudian Company; Plasticizer: A combination of polybutadiene and naphthenic oil in a mass ratio of 1:0.5; Antioxidant: A combination of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; Light stabilizer: UV-327, a UV absorber, purchased from Nanjing Bermuda Biotechnology Co., Ltd. Modified nano-calcium carbonate: 98g of raw material nano-calcium carbonate with an average particle diameter of 60nm was dried in an oven at 105℃ for 30min. The dried material was then put into a high-speed mixer, heated to 100℃, and 2g of stearic acid was added. The mixture was stirred at 1500r / min at 100℃ for 60min. After the mixing reaction was completed, the mixture was dried at 80℃ for 5h to obtain modified nano-calcium carbonate. Modified Hollow Microspheres-I: 100g of raw material hollow microspheres (50g each of raw material hollow glass microspheres and raw material hollow ceramic microspheres) with an average particle diameter of 20μm were added to a 6wt% NaOH aqueous solution and stirred for 3h; the resulting material was washed successively with a 2wt% acetic acid aqueous solution and water until neutral, and then dried at 80℃ for 8h; 3g of KH-570 was added to 500mL of ethanol aqueous solution with a volume ratio of 1:1 and stirred until fully dissolved to obtain a hydrolysis solution; the dried microspheres were added to the hydrolysis solution and stirred at 70℃ for 2h; the material separated by vacuum filtration was washed three times with ethanol to remove the physically adsorbed coupling agent, and the product was dried at 100℃ for 9h to prepare modified hollow microspheres-I; Modified hollow microspheres-II: The same method as that used to prepare modified hollow microspheres-I was employed, except that the raw material hollow microspheres were replaced with raw material hollow glass microspheres of the same particle size to prepare modified hollow microspheres-II. Functional filler-I: formed by combining modified nano-calcium carbonate and modified hollow microspheres-I in a mass ratio of 2:1; Functional filler-II: formed by combining modified nano-calcium carbonate and modified hollow microspheres-I in a mass ratio of 6:1; Functional filler-III: formed by combining modified nano-calcium carbonate and modified hollow microspheres-II in a mass ratio of 2:1; Functional filler-IV: formed by combining modified nano-calcium carbonate and modified hollow microspheres-I in a mass ratio of 1:1; Substrate: PP-EPE-PP three-layer composite waterproof and breathable base film, purchased from Jiangsu Freudenberg Building Energy Conservation Technology Co., Ltd. Isolation and protective layer: PE isolation film, purchased from Shanghai Qunqi Company.
[0047] Unless otherwise specified, the component amounts in the following examples are expressed in parts by weight, with each part by weight being 10g.
[0048] Preparation Example 1 This preparation example illustrates the preparation of the waterproof and breathable non-asphalt-based adhesive provided by the present invention, including the following steps: (1) The elastomer base material after drying treatment (drying temperature is 60℃ and time is 3h) is placed in a high-speed kneader and melt-mixed for 15min at a speed of 400rpm and a temperature of 120℃ to obtain elastomer melt; (2) Keep the temperature and rotation speed constant, add the thickening resin to the elastomer melt, stir and mix for 20 minutes, then add the plasticizer and stir and mix for 10 minutes to obtain material I; (3) Under the conditions of 600 rpm and 120℃, the modified nano calcium carbonate is first mixed with the material I, sheared and stirred for 20 min, then the modified hollow microspheres are added, and sheared and stirred for another 15 min to obtain material II; (4) At a speed of 400 rpm and a temperature of 140°C, the additives are mixed with the material II and stirred for 10 min to obtain the waterproof and breathable non-asphalt-based adhesive.
[0049] The specific types of substances, amounts, and process parameters for this preparation example are shown in Table 1.
[0050] Unless otherwise specified, Preparation Example 2 and Preparation Example 3 were carried out in accordance with the method of Preparation Example 1. The difference is that the types and amounts of substances used and the process parameters are not exactly the same in the examples. See Table 1 for details.
[0051] Table 1
[0052] Preparation Example 4 This preparation example was carried out using a method similar to that of Preparation Example 1. The difference is that in this preparation example, functional filler-III was used in equal parts by weight to replace functional filler-I in Preparation Example 1, resulting in waterproof and breathable non-asphalt-based adhesive-IV.
[0053] Preparation Example 5 This preparation example was carried out using a method similar to that of Preparation Example 1. The difference is that the elastomer base material in this preparation example is a combination of hydrogenated styrene-isoprene copolymer (SEPS) and ethylene-octene copolymer (POE) in a mass ratio of 1:0.4, resulting in a waterproof and breathable non-asphalt-based adhesive material-V.
[0054] Preparation Example 6 This preparation example was carried out using a method similar to that of Preparation Example 1. The difference is that the elastomer base material in this preparation example is a combination of hydrogenated styrene-isoprene copolymer (SEPS), ethylene-octene copolymer (POE), and ethylene-vinyl acetate copolymer (EVA) in a mass ratio of 1:0.1:0.8, resulting in a waterproof and breathable non-asphalt-based adhesive material -VI.
[0055] Comparative Preparation Example 1 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that the elastomer base material in this comparative preparation example is a combination of ethylene-octene copolymer (POE) and ethylene-vinyl acetate copolymer (EVA) in a mass ratio of 1:1, resulting in a non-asphalt-based rubber compound -DI.
[0056] Comparative Preparation Example 2 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that 10 parts by weight of hydrogenated styrene-isoprene copolymer (SEPS) was used to replace the elastomer base material in Preparation Example 1 to obtain a non-asphalt-based adhesive - DII.
[0057] Comparative preparation example 3 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that in this comparative preparation example, functional filler-IV was replaced with an equal part by weight of functional filler-I in Preparation Example 1 to obtain non-asphalt-based rubber compound-DIII.
[0058] Comparative preparation example 4 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that 47 parts by weight of modified nano-calcium carbonate were used to replace the functional filler-I in Preparation Example 1 to obtain a non-asphalt-based rubber compound-DIV.
[0059] Comparative preparation example 5 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that the amount of elastomer base material was adjusted to 5 parts by weight and the amount of functional filler was adjusted to 52 parts by weight to obtain non-asphalt-based rubber compound-DV.
[0060] Comparative preparation example 6 This comparative preparation example was prepared using a method similar to that of Preparation Example 1. The difference is that 47 parts by weight of heavy calcium carbonate were used to replace the functional filler-I in Preparation Example 1 to obtain a non-asphalt-based rubber compound-DVI.
[0061] Example 1 This embodiment illustrates the preparation of the waterproof and breathable non-asphalt-based waterproof membrane provided by the present invention, including the following steps: The waterproof and breathable non-asphalt-based adhesive compound-I is heated to 150℃ using a hot melt adhesive coating machine. The molten adhesive is then applied to both the upper and lower surfaces of the substrate, with the coating amount controlled at 220g / m². 2 Then, a PE release film is applied to the top and bottom surfaces after coating, and the thickness of the roll is controlled to be 1.2mm to obtain a waterproof and breathable non-asphalt-based waterproof roll.
[0062] Examples 2-6 The process was carried out in a similar manner to that of Example 1, except that the waterproof and breathable non-asphalt-based adhesives from Preparation Examples 2-6 were used to replace the waterproof and breathable non-asphalt-based adhesive-I in Example 1, and waterproof and breathable non-asphalt-based waterproof membranes were prepared.
[0063] Comparative Examples 1-6 The same method as in Example 1 was followed, except that the non-asphalt-based adhesives in Comparative Preparation Examples 1-6 were used to replace the waterproof and breathable non-asphalt-based adhesive-I in Example 1 to prepare the corresponding non-asphalt-based waterproof membranes.
[0064] Test case This test example performs performance tests on the non-bitumen-based waterproof membranes prepared in the above examples. Specifically: Adhesion performance test: The peel strength between the waterproof membrane and cement mortar was tested according to GB / T 35467-2017 standard. After soaking the sample of the waterproof membrane and cement mortar bonded together in water for 60 days, the peel strength retention rate between the waterproof membrane and cement mortar was determined. Weather resistance test: Referring to GB / T 18244-2022 and GB / T 35467-2017 standards, after the roll material is aged under a xenon lamp for 2500 hours, its maximum tensile strength retention rate and elongation retention rate at maximum tensile strength are tested; secondly, after the roll material is subjected to 200 cycles of thermal cycling at -20℃ and 80℃, its peel strength retention rate is determined.
[0065] Air permeability test: The equivalent air layer thickness S for water vapor diffusion was determined according to GB / T 17146-2015 standard. d ; Waterproof performance test: Refer to GB / T 23457-2017 standard, maintain constant pressure for 4 hours under a water pressure of 0.8MPa / 35mm, and determine whether there is leakage; under the above test conditions, extend the test time to 168 hours to determine whether there is leakage.
[0066] The test results are shown in Table 2.
[0067] Table 2
[0068] Continued from Table 2
[0069] The test results above show that the waterproof and breathable non-asphalt-based waterproof membrane prepared by the non-asphalt-based adhesive provided by the present invention has significantly better waterproof and breathable properties, weather resistance, and adhesion.
[0070] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A waterproof and breathable non-asphalt-based adhesive composition, characterized in that, The composition consists of a main agent and an auxiliary agent, wherein the main agent includes an elastomer base material, a tackifying resin, a plasticizer, and a functional filler; Based on the total mass of the composition, the content of the elastomer base material is 10-20 wt%, the content of the tackifying resin is 15-25 wt%, the content of the plasticizer is 15-20 wt%, and the content of the functional filler is 30-50 wt%. The elastomer base material includes a first component and a second component in a mass ratio of 1:0.3-1, wherein the first component is a hydrogenated styrene-isoprene copolymer and the second component is an ethylene-octene copolymer and / or an ethylene-vinyl acetate copolymer. The functional filler is formed by combining modified nano-calcium carbonate and modified hollow microspheres in a mass ratio of 2-6:1, wherein the modified hollow microspheres are modified hollow glass microspheres and / or modified hollow ceramic microspheres.
2. The composition according to claim 1, wherein, The elastomer base material is a combination of hydrogenated styrene-isoprene copolymer, ethylene-octene copolymer and ethylene-vinyl acetate copolymer in a mass ratio of 1:0.2-0.5:0.2-0.
5.
3. The composition according to claim 1 or 2, wherein, The styrene structural units in the hydrogenated styrene-isoprene copolymer are 36-40 wt%; And / or, the melt flow rate of the ethylene-octene copolymer at 190°C and 2.16 kg is 2-6 g / 10 min; And / or, the melt flow rate of the ethylene-vinyl acetate copolymer at 190°C and 2.16 kg is 350-400 g / 10 min, and the content of vinyl acetate structural units in the ethylene-vinyl acetate copolymer is 20-40 wt%.
4. The composition according to claim 1 or 2, wherein, In the functional filler, the modified nano-calcium carbonate is obtained by surface modification of raw nano-calcium carbonate with stearic acid, and the average particle diameter of the raw nano-calcium carbonate is 50-70 nm. And / or, in the functional filler, the modified hollow microspheres are a combination of modified hollow glass microspheres and modified hollow ceramic microspheres in a mass ratio of 1:0.8-1.2; And / or, in the functional filler, the modified hollow microspheres are obtained by hydrophobic modification of raw hollow microspheres with a silane coupling agent, and the average particle diameter of the raw hollow microspheres is 10-20 μm.
5. The composition according to claim 1 or 2, wherein, The tackifying resin is a combination of terpene phenolic resin and hydrogenated C5 petroleum resin in a mass ratio of 1.5-3:
1. And / or, the plasticizer is formed by compounding polybutadiene and naphthenic oil, wherein the molecular weight of the polybutadiene is 3000-3500.
6. The composition according to claim 1 or 2, wherein, The additives include antioxidants and light stabilizers; Based on the total mass of the composition, the content of the antioxidant is 1-2 wt%, and the content of the light stabilizer is 1-2 wt%.
7. A method for preparing a waterproof and breathable non-asphalt-based adhesive, characterized in that, The method is carried out using each component of the composition according to any one of claims 1-6, and the method includes: stirring and mixing each component of the composition to obtain the waterproof and breathable non-asphalt-based adhesive.
8. The waterproof and breathable non-asphalt-based adhesive prepared by the method of claim 7.
9. A waterproof and breathable non-bitumen-based waterproof membrane, characterized in that, The waterproof membrane includes a substrate, a waterproof adhesive layer, and a protective membrane; the waterproof adhesive layer is formed of the waterproof and breathable non-asphalt-based adhesive as described in claim 8. Preferably, the substrate is a PP-EPE-PP three-layer composite waterproof and breathable base film.
10. The application of the waterproof and breathable non-bitumen-based waterproof membrane according to claim 9 in the field of building waterproofing.